Do psychological fallacies influence trading in financial markets? Evidence from the foreign exchange market - Bleaney, Michael; Bougheas, Spiros; Zhiyong, Li (Taylor & Francis, 2017)
Research in both economics and psychology suggests that, when agents predict the next value of a random series, they frequently exhibit two types of biases, which are called the gambler’s fallacy (GF) and the hot hand fallacy (HHF). The gambler’s fallacy is to expect a negative correlation in a process which is in fact random. The hot hands fallacy is more or less the opposite of this – to believe that another heads is more likely after a run of heads. The evidence for these fallacies comes largely from situations where they are not punished (lotteries, casinos and laboratory experiments with random returns). In many real-world situations, such as in financial markets, succumbing to fallacies is costly, which gives an incentive to overcome them. The present study is based on high-frequency data from a market-maker in the foreign exchange market. Trading behaviour is only partly explained by the rational exploitation of past patterns in the data. There is also evidence of the gambler’s fallacy: a tendency to sell the dollar after it has risen persistently or strongly.